IGNEOUS ACTIVITY AND METALLOGENY OF STRUCTURAL AND ASSOCIATIONAL ZONES WITH SIALIC BASEMENT IN THE URALS EUGEOSYNCLINE - Smirnov V.N.; Korovko A.V.; Dvoyeglazov D.A. (My University, 1989)
Recent data indicate that even in the Urals, which constitute a reference femic type geosynclinal foldbelt, the geosynclinal structural and associational zones framing the ancient sialic blocks or microcontinents exhibit igneous rocks and endogenous metallogeny that differ from those in the principal, typically eugeosynclinal zones. In the present paper, the authors discuss the properties of such zones as exemplified by the Rezh structural and associational zone in the Central Urals.